Penerapan Konseling Islam Untuk Mengatasi Gangguan Kesehatan Mental Pada Lansia - Annisaa Rahmania Qurrota A'yun (Journal of Society Counseling, 2023)
In old age, getting mentally healthy is not easy, declining health status and physical abilities will cause the elderly to slowly withdraw from relationships with the surrounding community. This research is entitled "The Application of Islamic Counseling to Overcome Mental Health Disorders in the Elderly at Harapan Kita Social Institution". Mental health is the realization of genuine harmony between mental functions and the creation of self-adjustment between humans and themselves and their environment based on faith and piety and aims to achieve a meaningful and happy life in this world and the hereafter. This study aims to determine the description of mental health in the elderly and to determine the application of Islamic counseling with the Zikir method in overcoming mental health disorders in the elderly. This study uses a qualitative approach using a qualitative description research type. The subjects in this study were five elderly people. Data collection techniques, namely the method of observation, interviews, and documentation. The data analysis technique used is data reduction, data presentation, and drawing conclusions. The results of this study indicate that the picture of mental health in the elderly at Harapan Kita Social Institution is low health for the elderly which is characterized by irritability, being alone, irritable, feeling useless, always feeling lonely, like to think negative things about themselves and their lives. The application of Islamic counseling using the Zikir method was carried out in 6 meetings with 45 times/meeting. The implementation of Islamic counseling is carried out in three stages, namely the initial stage, the core/work stage, and the final stage.